Isolated plexiform neurofibroma over left palm: A case report and review of literature - Mohan H Kudur; Manjunath Hulmani (Wolters Kluwer Medknow Publications, 2013)
Plexiform neurofibroma is common over the branches of trigeminal and cervical nerves over the face. Plexiform neurofibroma over palm is rare and affects the individuals with fine motor functions of hand. Here, we report a case of isolated plexiform neurofibroma over the palm with review of literature.